MANAJEMEN MUTU PELAYANAN PENDIDIKAN - Wasisto, Edhi (KELOLA, 2013)
This study aimed to determine the effect of service quality in terms of the dimensions of tangibles, reliability, responsiveness, assurance, empathy and body image influenced on student loyalty with satisfaction as an intervening variable. Data were collected from 42 respondents using accidental sampling method sampling. Data analysis was carried out through analysis of research instruments that include test 0f validity of using the product moment correlation and reliability testing using Cronbachs alpha technique, the normality test, test lineritas, hypothesis test includes multiple linear regression, t test, F test and coefficient of determination (R2). From the analysis of data obtained the following results: variable responsiveness, assurance, and the image of the institution emphaty had a positive significant influence on student satisfaction, while tangibles and reliability had not a significant and negative effect on student satisfaction. Variable reliability, responsiveness, assurance, and the image of the institution emphaty had a positive and significant influenced on student loyalty satisfaction while tangibles variable had a negative and was not significant to student loyalty. Effect of total R 2 0.982, or 98.2%. Satisfaction variable could not be an intervening variable between reliability, responsiveness, assurance, and the image of the institution emphaty loyalty. Key word : reliability, responsiveness, assurance, emphaty and loyalty.